Kitüntetésadományozások Ausztria-Magyarország zsidó katonái részére a Nagy Háborúban - Bíró Ákos; „A királyhűség jól bevált útján...” Rendi és nemzeti kötődések szimbolikus változásai 1867 és 1918 között (2014) (Szeged) (2016)
Heroism and bravery has been measured by certain decorations by the Emperor-King of Austria-Hungary since the 18th century, and even earlier, however, the origins of most Austro-Hungarian orders and medals root in the rococo era of the Empire. As part of the equality process, from the first half of the 19th Century the military became more and more opened for Jewish soldiers, and by the second half of the century the presence of Jewish officers and NCOs as well as simple soldiers became common in every branch and rank within the whole of the Armed Forces. While in the civilian life this equality was often questioned, the military offered a chance for any brave Jewish soldier to excel and distinguish himself, regardless of nationality, faith, or beliefs. In my study, I will try to examine the contemporary literature, the data which was published between 1920-1944 about the decorations which were awarded to Jewish soldiers, and correct them, as most of those are regretfully do not correspond with other relevant and proven information we have available from other sources.
Keywords: Bölcsészettudományok; Történettudomány és régészet